Knowledge and Attitudes About Emergency Contraception Among Married Women in the Eastern Black Sea Region of Turkey - Yeşim Bayoğlu Tekin; Ülkü Mete Ural; Işık Üstüner; Gülşah Balık; Figen Kır Şahin; Emine Seda Güvendağ Güven (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: Emergency contraception (EC) is an effective contraceptive method that can be used after having unprotected intercourse to prevent the implantation of the unintended pregnancy. We aimed to evaluate the knowledge level of reproductive aged women about EC pills and its relation to the contraceptive attitudes and personal characteristics.